Bahasa arab sebagai alat diplomasi budaya: Studi kasus di negara-negara Timur Tengah - Azzam, Abdullah (Maliki Interdisciplinary Journal, 2024)
The Arabic language plays a crucial role in cultural diplomacy in Middle Eastern countries. This article analyzes how Arabic is utilized as a tool to facilitate diplomatic relations and enhance cross-cultural understanding. Through case studies in several Middle Eastern nations, this research identifies various strategies employed by governments and cultural institutions to promote Arabic as a means of diplomacy. Findings reveal that teaching Arabic to foreign diplomats, translating Arabic literary works into other languages, and organizing cultural events that highlight the Arabic language significantly contribute to strengthening international relations. Additionally, Arabic serves as a symbol of identity and national pride, reinforcing solidarity among Arab nations. The article underscores the importance of language as a vital component in cultural diplomacy and recommends increased investment in Arabic language education programs to support diplomatic efforts. Thus, Arabic becomes not only a means of communication but also a crucial bridge connecting diverse cultures on the global stage.